Emulsions with heavy crude oil in presence of nanoparticles (2014)
A study about the use of silica nanoparticles in crude oils from the Castilla field and the effects on stability, drop size and emulsion viscosity was carried out. The interest in the use of this type of nanoparticles is created by the inversion effect that these produce in the W/O emulsion at high water cuts upper than 48%. The emulsion is transformed in W/O/W being the latter the least viscous due to the water is the external phase and it allows to the crude oil slides easily on any surface. In this study, two types of naturally emulsified crude oil with different water cuts and a synthetic emulsion were used. This kind of behavior created by nanoparticles over the emulsion could be an alternative solution to the viscosity, fluidity and mobility problems that affect the extraction and transportation in heavy crude oil.